Assessment of the frequency criterion for the diagnosis of non-suicidal self-injury disorder in female adolescents with conduct disorder. (September 2018) - Szewczuk-Bogusławska, Monika; Kaczmarek-Fojtar, Małgorzata; Moustafa, Ahmed A.; Mahlberg, Justin; Frydecka, Dorota; Oleszkowicz, Anna; Bąk, Olga; Misiak, Błażej
Highlights: The frequency threshold of non-suicidal self-injury disorder might be insufficient. At least 8 self-injuries in the last year should be considered as a criterion. Depressive symptoms characterize repetitive self-injurers with CD. Abstract: Recent studies suggest a higher threshold number of self-injuries during the past year than the one proposed in the DSM-5 criteria for non-suicidal self-injury disorder (NSSID). Therefore, we aimed to test a validity of the frequency criterion in girls with conduct disorder (CD) based on psychopathology and the level of functioning. Mixture modelling analysis revealed that the frequency of at least 8 self-harm behaviours in the previous year differentiated adolescents with CD. Thus, we divided adolescents into three subgroups: group 1: at least 8 self-harm acts; group 2: 1–7 self-harm behaviours and group 3: those who did not injure themselves during the last 12 months. Individuals from group 1 were significantly younger and had earlier age of self-harm onset. There were significant differences between groups 1 and 3 in terms of anxiety and depressive symptoms, self-esteem, aggression and the global functioning level. The group 1 scored significantly higher on depressive symptoms compared to the group 2. The group 2 scored significantly higher than the group 3 on the level of hostility. Our results provide further evidence supporting the need for modification of the NSSID frequency criterion.